Preliminar reflections about a present techno medical application: clonation - Arranz, José Antonio; Ariza, Xavier; Riudor, Encarnació; Vilar, Lluis; Salvadó, Jordi; Galofré, Núria; Vendrell, Susana; Esquirol, Josep Maria (Acta Bioethica, 2003)
This paper reflects about the new medical technoscience challenge opened: the possibility of therapeutic or reproductive clonation. The present paper approximates the medical-scientific terminology clearly and schematically, from the concepts of sexual or asexual reproduction to endonucleation, to the concepts of germinal, somatic or in vitro embryos and stem cells, to carry out an analysis of the ethical conflicts opened in each case. The last part of the essay centers in ethical issues related to the embryo, particularly the problems generated by the surplus embryos of fertilization in vitro research, different social groups, that opposed to their use, and the law, that declares them unusabel for reproductive purposes when their viability cannot be guaranteed. , origin of an important controversy between the scientific community, that would like that they be utilized for